Barriers To Healthcare For Sri Lankan Tamil Refugees In Tamil Nadu, India - et. al., Maneesh P, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Health is a fundamental human right and is also considered as a worldwide social goal. It is an important determinant of well being and healthcare is regarded as a public right, and an important responsibility of governments to provide this care to all people irrespective of race, religion, caste or creed, rural or urban, rich or poor. In India, the effort to improve the health status of the population is a major thrust and it is under the social development programmes being undertaken in India. Public health programmes play a very significant role in the physical and mental well being of the citizens of every nation. The improvement of the health status of people is connected to several factors such as household income, public expenditure on healthcare delivery system, availability of private healthcare facilities and general environmental conditions affecting the incidence of diseases. The health status of the population of a nation was assumed to affect the utility of the people directly by the value that individuals place on good health and indirectly through increasing healthy time and labour income of the person [1]. Unlike the health services available to the citizens, the same services are not made available to refugees who are living in the country. This study attempted to analyse the extent and issues of health care access and the health concern of Sri Lankan Tamil camp living refugees in Thiruvannamalai and Vellore district. For the study, Pethi Kuppam refugee camp in Thiruvallur district and Kasthambadi camp in Tiruvannamalai district were selected. Due to the restriction in entering the camp, the interview was conducted outside of the camps and respondents were selected through the convenience sampling method. Thirty camp inmates were interviewed with the help of a semi-structured interview schedule. The study revealed that the location of the camp is one of the major determinants of health care access. The people living in the camp of rural area need to travel long hours to access health care. The government health care services to refugees are inadequate and improper. There is a delay in receiving the benefit of health care schemes and the procedures for application is complicated. Besides, refugees are manual labourers and they remain unemployed for half of every month. Therefore, the problem of affordability came into existence. An intervention on the part of the government is required to facilitate adequate health care services for the refugees and health insurance should be extended to them also.